Public engagement in decision‐making regarding the management of the COVID‐19 epidemic: Views and expectations of the 'publics' - Sophie Kemper; Frank Kupper; Sandra Kengne Kamga; Anne Brabers; Judith De Jong; Marloes Bongers; Aura Timen (Wiley, 2022)
Abstract Background In the management of epidemics, like COVID‐19, trade‐offs have to be made between reducing mortality and morbidity and minimizing socioeconomic and political consequences. Traditionally, epidemic management (EM) has been guided and executed attentively by experts and policymakers. It can, however, still be controversial in the public sphere. In the last decades, public engagement (PE) has been successfully applied in various aspects of healthcare. This leads to the question if PE could be implemented in EM decision‐making. Methods From June to October 2020, seven deliberative discussion focus groups were executed with 35 Dutch citizens between 19 and 84 years old. Their views on PE in COVID‐19 management were explored. The deliberative approach allows for the education of participants on the topic before the discussion. The benefits, barriers, timing and possible forms of PE in EM were discussed. Results Almost all participants supported PE in EM, as they thought that integrating their experiences and ideas would benefit the quality of EM, and increase awareness and acceptance of measures. A fitting mode for PE was consultation, as it was deemed important to provide the public with possibilities to share ideas and feedback; however, final authority remained with experts. The publics could particularly provide input about communication campaigns and control measures. PE could be executed after the first acute phase of the epidemic and during evaluations. Conclusions This paper describes the construction of an empirically informed framework about the values and conditions for PE in EM from the perspective of the public. Participants expressed support to engage certain population groups and considered it valuable for the quality and effectiveness of EM; however, they expressed doubts about the feasibility of PE and the capabilities of citizens. In future studies, these results should be confirmed by a broader audience. Patient or Public Contribution No patients or members of the public were involved in the construction and execution of this study. This study was very exploratory, to gain a first insight into the views of the public in the Netherlands, and will be used to develop engagement practices accordingly. At this stage, the involvement of the public was not yet appropriate.